Accounting Information System And Prevention Of Fraudulent Drug Supply At The Kardinah Tegal General Hospital - Setiyorini, Ika; Susilawati, Desi (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to determine the application of accounting information systems, internal control, factors causing stock outs, and prevention of fraud in drug supplies at Kardinah Tegal Hospital. Data collection methods used in this study were observation, interviews, and documentation. The data used consists of primary data and secondary data. The data analysis technique used is descriptive qualitative method. The results of the study explain that the application of the accounting information system for drug supplies as a whole is good, including: 1) Kardinah Hospital Tegal has operated a Pharmacy Hospital Management Information System (SIMRS) as an information system and efficient management of medicines starting from planning, procurement, receipt , distribution, and administration of invoice payments, 2) There are SOPs related to the logistics management of pharmaceutical supplies, out-of-stock handling procedures that aim to improve optimal prescription services but in practice there are inconsistencies with SOPs so it is recommended for SOP revisions, 3) The current internal control has been appropriate and has implemented internal control standards according to the Committee of Sponsoring Organization (COSO), and 4) The factors causing the scarcity of medicine supplies include vacancies at distributors, delays in delivery of goods, late payments to partners, and na available is not sufficient. To prevent fraud, Kardinah Tegal Hospital must implement healthy practices to minimize fraud, both internally and externally.